2019
DOI: 10.1021/acs.jmedchem.9b00616
|View full text |Cite
|
Sign up to set email alerts
|

Late-Stage Functionalization of Platensimycin Leading to Multiple Analogues with Improved Antibacterial Activity in Vitro and in Vivo

Abstract: Bacterial fatty acid synthases are promising antibacterial targets against multi-drug resistant pathogens. Platensimycin (PTM) is a potent FabB/FabF inhibitor, while its poor pharmacokinetics hampers the clinical development. In this study, a focused library of PTM derivatives was prepared through thiolysis of PTM oxirane (1), followed by various C−C cross-coupling reactions in high yields. Antibacterial screening of these compounds in vitro yielded multiple hits with improved anti-Staphylococcus activities ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…MRSA-infected mice treated with 10 mg/kg of PTM survived on the same day of MRSA infection, but all died on day 2. Consistent with our previous report, 23,24 these data suggested that PTM might have limited antibacterial activity in vivo by intraperitoneal injection, in contrast to the inconvenient continuous infusion route reported by Singh and coworkers. 15 Treatment of infected mice by 10 mg/kg of Lip/ PTM, M-Lip/PTM, or PLGA−PEOz/PTM led to higher survival rates of 20% to 40%, suggesting the improved in vivo efficacy over PTM.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…MRSA-infected mice treated with 10 mg/kg of PTM survived on the same day of MRSA infection, but all died on day 2. Consistent with our previous report, 23,24 these data suggested that PTM might have limited antibacterial activity in vivo by intraperitoneal injection, in contrast to the inconvenient continuous infusion route reported by Singh and coworkers. 15 Treatment of infected mice by 10 mg/kg of Lip/ PTM, M-Lip/PTM, or PLGA−PEOz/PTM led to higher survival rates of 20% to 40%, suggesting the improved in vivo efficacy over PTM.…”
Section: Resultssupporting
confidence: 92%
“…The mouse model of acute infectious peritonitis was established by intraperitoneal injection of MRSA (2.5 × 10 7 CFU/per mouse), as previously reported (Figure 6A). 23,24 As shown in Figure 6B, the infected mice treated with saline died on the same day of the infection, while mice treated by vancomycin survived 7 days. MRSA-infected mice treated with 10 mg/kg of PTM survived on the same day of MRSA infection, but all died on day 2.…”
Section: Resultsmentioning
confidence: 95%
“…For platensimycin, this includes the modifications of the benzoic acid head group[ 26 , 27 ] and the tetracyclic cage. [ 28 , 29 , 30 , 31 , 32 ] While some of these compounds showed promising activity against Gram‐positive bacteria, for most compounds activity against Gram‐negative bacteria was not reported. In addition, poor pharmacokinetic properties were also a concern.…”
Section: Introductionmentioning
confidence: 99%
“…Total synthesis of platencin [22,23] and platensimycin [24,25] have been carried out, and efforts have been undertaken to increase the antibiotic activity through synthesis of analogues. For platensimycin, this includes the modifications of the benzoic acid head group [26,27] and the tetracyclic cage [28–32] . While some of these compounds showed promising activity against Gram‐positive bacteria, for most compounds activity against Gram‐negative bacteria was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…For platensimycin this includes the modifications of the benzoic acid head group [28,29] and the tetracyclic cage. [30][31][32][33][34] While some of these compounds showed promising activity against Gram-positive bacteria, for most compounds the potency activity against Gram-negative bacteria was not reported. In addition, poor pharmacokinetic properties were also a concern.…”
Section: Introductionmentioning
confidence: 99%